2014
DOI: 10.2139/ssrn.2509285
|View full text |Cite
|
Sign up to set email alerts
|

Job Creation, Firm Creation, and <I>De Novo</I> Entry

Abstract: Firm turnover and growth recorded in administrative data sets differ from underlying firm dynamics. By tracing the employment history of the workforce of new and disappearing administrative firm identifiers, we can accurately identify de novo entrants and true economic exits, even when firms change identifier, merge, or split-up. For a well-defined group of new firms entering the Belgian economy between 2004 and 2011, we find highly regular post-entry employment dynamics in spite of the volatile macroeconomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…The idea underlying this data construction exercise is to exploit payroll data to track workers across different firm identifiers; if a high percentage of workers in an exiting business at time t is found to be recorded under a new firm at time t+1, then the two observations are considered to be from the same business. Similar techniques have been used in other countries, also to identify outsourcing and insourcing patterns: in the United States as described in Benedetto et al (2007), in Belgium (see Geurts and Van Biesebroeck, 2013), in Denmark (Ibsen and Westergaard-Nielsen, 2011) and in Germany (at the establishment level: Hethey-Maier and Schmieder, 2013). 12 The US Census uses a different approach to compute establishment and firm age from the data in the Longitudinal Business Database (LBD) (see Becker et al, 2006;and Davis et al, 2007).…”
Section: Challenges With Measuring Firm Entry and Agementioning
confidence: 99%
“…The idea underlying this data construction exercise is to exploit payroll data to track workers across different firm identifiers; if a high percentage of workers in an exiting business at time t is found to be recorded under a new firm at time t+1, then the two observations are considered to be from the same business. Similar techniques have been used in other countries, also to identify outsourcing and insourcing patterns: in the United States as described in Benedetto et al (2007), in Belgium (see Geurts and Van Biesebroeck, 2013), in Denmark (Ibsen and Westergaard-Nielsen, 2011) and in Germany (at the establishment level: Hethey-Maier and Schmieder, 2013). 12 The US Census uses a different approach to compute establishment and firm age from the data in the Longitudinal Business Database (LBD) (see Becker et al, 2006;and Davis et al, 2007).…”
Section: Challenges With Measuring Firm Entry and Agementioning
confidence: 99%
“…However, small start-ups are generally more likely to be genuinely new firms (de-novo entry) as compared to larger entrants, which are relatively more likely to be the result of mergers or acquisitions or legal rather than economic changes in the life of a firm (i.e., de-alio entry; see Geurts and Van Biesebroeck, 2013). For this reason, all graphs reporting statistics relative to all entrants are replicated in Annex B limiting the selection only to small units (e.g., below 50 employees) for those countries for which data availability allows it.…”
mentioning
confidence: 99%
“…for firms involved in an event in a given period t-1 to t. In the next period, we restart from registered employment in t and impute employment in t+1 for events in that period. Geurts and Van Biesebroeck (2014) have extended the imputation method over a five-year period. They found that firm ID numbers involved in a linkage event are more likely to be involved in another event in one of the following years.…”
Section: Recalculating Measures Of Entry Exit and Growthmentioning
confidence: 99%
“…Spurious entrants and exits are eight times larger on average than real entrants and exits (Table A.2 in the Appendix). Other studies have demonstrated that entry and exit from ID changes, firm restructurings or diversifying firms also differ in characteristics other than size, such as in the determinants of entry (Acs and Audretsch 1989;Storey 1991), post-entry growth patterns (Mata et al 1995;Geurts and Van Biesebroeck 2014), or the profitably and productivity at exit (Baldwin and Gorecki 1987).…”
Section: Spurious Entrants and Exits By Sizementioning
confidence: 99%
See 1 more Smart Citation